The association between alcohol consumption and prevalent cardiovascular diseases among HIV-infected and HIV-uninfected men. - Freiberg, Matthew S; McGinnis, Kathleen A; Kraemer, Kevin; Samet, Jeffrey H; Conigliaro, Joseph; Curtis Ellison, R; Bryant, Kendall; Kuller, Lewis H; Justice, Amy C (Journal of acquired immune deficiency syndromes (1999), 2010)
To determine whether alcohol consumption is associated with cardiovascular disease (CVD) among HIV-infected veterans.
Keywords: Alcohol Drinking; Alcoholism; Cardiovascular Diseases; Cohort Studies; HIV Infections; Humans; Male; Prevalence; Risk Factors